Recent advances and prospects toward blue perovskite materials and light‐emitting diodes. Issue 2 (3rd July 2019) - Fang, Tao; Zhang, Fengjuan; Yuan, Shichen; Zeng, Haibo; Song, Jizhong
Abstract: Perovskite based light‐emitting diodes (PeLEDs) have become a powerful candidate for next‐generation solid‐state lightings and high‐definition displays due to their high photoluminescence quantum yield (PLQY), tunable emission wavelength over the visible spectrum, and narrow emission linewidths. Over the past few years, the development of red‐ and green‐emissive PeLEDs has rapidly increased, and the corresponding external quantum efficiencies (EQE) have exceeded 20%. However, the research progress of blue‐emitting PeLEDs is limited by its poor material quality and inappropriate device structure. Currently, the maximum EQE of blue PeLED is only 6.2%, which is far from the industrialization requirements. In order to promote the development of blue PeLEDs, we summarize the recent research progress of blue perovskite materials and LEDs and discuss several fatal challenges, mainly embodied in low efficiency and poor stability. In order to overcome these challenges, detailed analysis and strategies are put forward in terms of the materials and devices. For the former, we summarize the feasible strategy for the preparation of efficient and stable blue‐emissive perovskites using component engineering. For the latter, we analyze the advantages and limitations of the different strategies for blue‐emissive perovskite in LEDs. At the end of the review, a comprehensive outlook is detailed, including future development directions and several technical problems to be solved. Thus, we aim to highlight the significance and promote the industrialization of PeLEDs. Abstract : Perovskite light‐emitting diodes (PeLEDs) are promising for future high‐quality lightings and displays due to narrow light‐emitting peak, precise tunable color, and photoluminescence efficiency. However, the performance of blue PeLEDs is considerably behind red and green devices. In this review, the development status and issue of blue‐emitting perovskite materials and LEDs are summarized, and the future challenges and feasible outlooks are highlighted.